Foliar epidermal and pollen characters in the genus Cola Schott. & Endl. in Nigeria (2005)
The leaf epidermal and pollen characters of eight Cola species in Nigeria were studied by light microscopy for the purpose of identification of the species even in fragmentary and sterile state. The epidermal cells were polygonal in shape except in C. glabra where they were irregular. The anticlinal walls were straight (C. gigantea), undulate (C. glabra) and straight to slightly curved in the others. C. acuminata, C. laurifolia and C. nitida were amphistomatic while the others were hypostomatic. Stomatal types were anisocytic (C. flaviflora), anomocytic (C. glabra), laterocytic (C. hispida) but stattrocylic in the others. Crystal sands were present in C. hispida. C. flaviflora (24-09) and C. hispida (42-110) had the lowest number of epidermal cells/mm2 while the highest occurred in C. millenii (720-950). Conversely, C. flaviflora (24-50µm) and C. hispida (29-60µm) had the widest celts. The highest stomatal densities occurred likewise in C. hispida and C. gigantea (72-121) but the lowest were found in C. flaviflora (24-70). Whereas. C. acuminata recorded the largest stomata (24-26 x 15-17µm), it had the lowest stomatal index (15.7%). The highest index (60.6%) was found in C. hispida while the smallest stomata belonged to C. laurifolia (9-12 x 9- l lµm). Trichomes, though absent in all the taxa, the bases were present in them and very prominent in C. gigantea. The pollen grains were either subprolale or prolate, spheroidal. The presence and number of pores and furrows varied in the species, tricolporate (C. acuminata, C. gigantea and C. hispida), dicolporate (C. flaviflora, C. millenii and C. nitida) and inaperturate (C. glabra and C. laurifolia). The combination of these various micro-morphological characters is useful for the delimitation and identification of the species even in their fragmentary state.